Empowerment of the Curah Indah Farmers Group in Banyuwangi through the Processing of Cascara Tea as a Functional Beverage Modified from Coffee Husk Waste: Pemberdayaan Kelompok Tani Curah Indah Banyuwangi Dalam Pengolahan Teh Cascara Sebagai Minuman Fungsional Termodifikasi Dari Limbah Kulit Kopi - Purwaningtyas, Ayu; Utami, Sari Wiji; Setiadevi, Shinta (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Macan Putih is one of the coffee producing areas in Banyuwangi with the coffee variety produced being Robusta coffee. Coffee in this area has the potential to improve community welfare which is developed as a joint farming activity under the Curah Indah Farmers Group. However, the use of coffee by the Curah Indah Farmers Group is still limited to processing it in the form of coffee logs or beans in the form of green beans that have not been roasted. The process of processing coffee cherries into green beans produces 65% coffee beans and 35% coffee skin waste. This waste is usually thrown in the yard or in waterways, causing a bad smell because the coffee skin still has a fairly high air content, namely 75-80%. This makes it easier for spoilage microbes to grow. If this condition is not handled properly, it will cause soil and air pollution, which can disrupt public health and the environment around where you live. Coffee skin waste in Macan Putih has not been utilized due to the limited knowledge possessed by the Curah Indah Farmers Group. For this reason, the Poliwangi Team's PKM activities provide a solution for utilizing coffee husk waste in the form of making Cascara tea as a functional drink that is packaged attractively, so that it has added value for marketing. The content of coffee skin waste in the form of antioxidants, caffeine, and cholorogenic acid is able to maintain the digestive tract, reduce blood sugar levels, inhibit cancer cells, and maintain heart health. The technique for making Cascara tea is done by adding cinnamon, so it has a high antioxidant content. Cascara tea is made as a souvenir (something to buy) for tourists and supplies the needs of guests (amenities) staying at hotels, resorts and homestays in Banyuwangi